Angiotensin converting enzyme activity in the serum, lung, liver and kidney in streptozotocin-induced diabetic rats and diabetic nephropathy - Ustundag, B.; Cay, M.; Ozercan, I.H.; Naziroglu, M.; Ilhan, N. (My University, 1998)
To clarify the relationship between the alterations of the levels of angiotensin converting enzyme (ACE) and diabetic nephropathy, ACE activity in the lung, liver, kidney and serum were investigated in streptozotocin (STZ)- induced diabetic rats. The levels of serum ACE activity unchanged 3 days post STZ treatment but it was significantly an increase 12 and 30 days post STZ treatment in diabetic rats (p<0.001). Lung ACE activity was significantly increased at 12 and 30 days post STZ Treatment in diabetic rats (P<0.05 and P<0.005). There was not showed an increase in the liver ACE activity at 3 and 12 days in diabetic rats such it was significantly elevated at 30 day in diabetic rats (P<0.05). Kidney ACE activity was significantly elevated at 12 day post STZ treatment in diabetic rats, whereas were not occurred significantly an increase at 3 and 30 days in diabetic rats (p<0.05). Histopathologic examination of the kidneys showed that thickening of the glomerular basement membrane, glomerular sclerosis, tubular dilatation and 'Capsular Cap' occurred in the kidneys of STZ-induced-diabetic rats at 12 and 30 days. In summary, it can be considered that high serum, lung and kidney ACE activity levels were related to with the complications in diabetic rats.
Keywords: Angiotensin Converting Enzyme; Nephropathy; Streptozotocin-Diabetes